Determinación molecular del virus de la diarrea viral bovina mediante rt-pcr en bovinos de la provincia de El Oro. - Cordova Lazo, Gabriel Eduardo (Machala : Universidad Técnica de Machala, 2024)
This study focuses on the molecular identification of bovine viral diarrhea virus (BVDV) in cattle from the province of El Oro, Ecuador, using the RT-PCR technique. Bovine viral diarrhea is a highly contagious disease that significantly impacts livestock productivity and reproductive health, leading to considerable economic losses. The research aimed to standardize the RT-PCR molecular technique for diagnosing BVDV. Several farms in the province of El Oro were sampled, and the samples were analyzed to determine the presence of BVDV. The results revealed a prevalence of 29% in the province, identifying the presence of BVDV in animals that, although not showing evident symptoms, were carriers and contributed to the spread of the virus. This study underscores the importance of implementing precise molecular techniques like RT-PCR to improve the detection and control of BVDV, especially in PI animals that may go unnoticed with traditional methods. The standardization of this technique in Ecuador could be established as the "Gold Standard" for BVDV diagnosis.
El presente estudio se enfoca en la identificación molecular del virus de la diarrea viral bovina (VDVB) en bovinos de la provincia de El Oro, Ecuador, utilizando la técnica de RT-PCR. La diarrea viral bovina es una enfermedad altamente contagiosa que afecta significativamente la productividad y salud reproductiva del ganado, causando pérdidas económicas considerables. La investigación se centró en estandarizar la técnica molecular de RT-PCR para el diagnóstico del VDVB. Se muestrearon varias haciendas en la provincia de El Oro y se analizaron las muestras para determinar la presencia del VDVB. Los resultados revelaron una prevalencia del 29% en la Provincia, identificando la presencia del VDVB en animales que, aunque no presentaban síntomas evidentes, eran portadores y contribuían a la diseminación del virus. Este estudio subraya la importancia de implementar técnicas moleculares precisas como la RT-PCR para mejorar la detección y control del VDVB, especialmente en animales PI que pueden pasar desapercibidos con métodos tradicionales. La estandarización de esta técnica en Ecuador podría establecerse como un "Gold Standard" para el diagnóstico del VDVB.
Keywords: RT-PCR; VDVB; ANIMALES PI; MOLECULAR